Development of chitosan based adsorbent for removal of oil from industrial wastewater - Yunus, Rosli Mohd; Razali, Mohd Najib; Jemaat, Zulkifly (2012)
Monoethanolamine (MEA) is commonly used in oil and gas industry as absorption medium to remove carbon dioxide (C02) from gaseous stream. Upon usage, the MEA solution is contaminated with hydrocarbon and suspended solids. Heavily contaminated MEA solution reduces its effectiveness in stripping the C02 gas and also causes foaming phenomenon in the C02 removal unit which further reduces the overall performance of the unit. There are many instances in which during operation, the solution overshoot and mix with condensed water in the knock-out drum. At this point, all the solution (the contaminated solution and the condensed water) is discharged as wastewater and replaced with fresh solution. It is common, in the range of 60 to 80 tons of MEA wastewater is generated per month. This study was conducted to examine the best method of treating the MEA wastewater for the best interest of the company. Characterization of the MEA wastewater suggested that the most rational way of treating the wastewater was to achieve quality suited for the purpose of recycling it back into the system. Adsorption method was used for the treatment with four different types of adsorbent, namely chitosan, activated carbon, alum and zeolite, were investigated. Five different variables, namely adsorbent dosage, pH, temperature, mixing time and mixing speed were varied to examine the effect on the parameters such as percentage of residue oil, suspended solids, MEA concentration and COD level. The results showed that chitosan was the best adsorbent in treating the MEA wastewater, followed by activated carbon, alum and zeolite. Adsorbent dosage was the main variable affecting the performance of the adsorbent in removing the residue oil, suspended solids and reducing the COD level. Chitosan indicated two mechanisms of adsorption in treating the MEA wastewater, in which at low adsorbent dosage chitosan functioned through chemical adsorption, while at high dosage, electrostatic adsorption started to accompany. In all adsorbents investigated in this study, MEA concentration was not affected by the adsorption treatment. Through RSM optimization method conducted on the chitosan adsorption system revealed that with 300 ml volume of wastewater and optimum chitosan dosage of 5.92 wt%, residue oil reached its highest removal percentage of 98.77%, suspended solids removed by 58.79% and COD reduction of 85.52%.